Probing Anisotropic Quasiparticle Dynamics and Topological Phase Transitions in Quasi‐1D Topological Insulator ZrTe5 - Yueying Hou; Linze Li; Sutao Sun; Gan Liu; Hongyuan Zhao; Zhiheng Chen; Xuejun Yan; Yang‐Yang Lv; Yurong Yang; Shu‐Hua Yao; Jian Zhou; Y.B. Chen; et al. (Advanced Science)
Abstract The transition metal pentatelluride ZrTe5 exhibits rich lattice‐sensitive topological electronic states, and demonstrates great potential in photoelectric and thermoelectric devices. However, a comprehensive investigation of electron‐phonon coupling and phonon scattering process remains limited, despite their importance for transport properties and device optimization. Here, the hot carrier dynamics and a 1.15 THz Ag mode coherent phonon in ZrTe5 are investigated by femtosecond transient spectroscopy across 10–300 K. Notably, polarization‐dependent measurements explicitly decouple a strong anisotropic transient response, which is attributed to the effects of excited‐state electron relaxation and reflectivity modulation by displacive excited coherent phonons. The temperature dependence of electron relaxation time in ZrTe5 shows an inflection point, first offering the ultrafast dynamical signature of a temperature‐driven Lifshitz transition. At low temperatures, a long‐lived electron relaxation component emerges in the transient response, providing possible evidence of topological surface states in ZrTe5. In addition, the temperature‐dependent coherent phonon is also analyzed, revealing that its scattering is dominated by three‐phonon interactions and exhibits a relatively long lifetime compared to other modes. This work deepens the understanding of ultrafast processes in ZrTe5, resolves longstanding questions, paves the way for studying electronic phase transitions, and advances ZrTe5's application in optoelectronic and quantum devices.